Pendidikan Politik dari Partai Demokrasi Indonesia Perjuangan (PDIP) Kepada Generasi Muda di Kabupaten Halmahera Utara - J. Lain , Laurens (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research explores the political education of the Indonesian Democratic Party of Struggle (PDIP) to the younger generation in North Halmahera Regency. An interview with the Chairman of the DPC PDI-P North Halmahera showed that PDIP recognizes the importance of political education to increase political awareness and community participation. The party carries the ideology of "Soekarnoism" with a focus on "Soekarno’s marhaeinism" as the basis for regeneration. The research used a qualitative approach to gain in-depth insight into the political education of the PDIP. The political education program is expected to increase the active participation of the younger generation in the political process and have implications for community development. However, this research has limitations by only interviewing one informant, so further research needs to be done by involving a broader perspective from party members and participants of the political education program